CURRENT ASPECT OF METAL-CERAMIC-BIOMATERIAL RESTORATIONS AND TECHNOLOGY - Irina Gradinaru; Raluca Jipu; Loredana Liliana Hurjui; Arina Alice Ciocan Pendefunda; Adina Oana Armencia; Mihaela Mitrea; Magda-Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2020)
Regardless the etiology, location, extent or topography, edentation is a pathological entity that, through evolution and complications, causes serious imbalances in the stomatognathic system. The restoration of specific homeostasis involves the satisfaction of the laws of geometric and biomechanical balance by restoring the initial mechanical parameters and the basic constants of the stomatognathic system represented by the posture relation, the centric relation, the occlusion relation and the small mandibular dyna. The design and implementation of the rehabilitation of fixed prosthetics must take into account the real needensuring a long-lasting congruence between the prosthetic part and the tissues of the stomatognathic system, but also ensuring an optimal resistance to environmental stresses. Although the concepts underlying the principles listed are different, each of them incorporates elements of significance for the biomechanical balancing of the dento-prosthetic assembly. One of the main prophylactic problems is the discerning use of dento-periodontal or, as the case may be, muco-osseous support, in order to disperse as much as possible the pressure and traction forces on the different elements of the prosthetic field.The observance of the curative principle presupposes the obtaining of a morpho-functional restoration capable of ensuring the resumption of the altered functions, in optimal conditions. The individualized occlusal modeling and in correct relation with the antagonistic teeth will contribute to the most physiological transmission of the masticatory forces to the maxillary bone bases.